The effect of financial technology on the sustainability of banks in the Gulf Cooperation Council countries - Aws AlHares (17541741) (2022)
The purpose of this study is to investigate the influence that financial technology (FinTech) companies have on the soundness of bank finances. Using a sample of 480 bank-year observation from an emerging market of the Gulf Cooperation Council (GCC) over the period of 2006–2021, we find that the development of FinTech firms over time increases bank financial stability. The study used the Refinitiv Eikon and Fintch Connect databases to measure variables. When we conduct sub-sample analyses by bank size, bank type, and level of corporate governance, we find additional evidence that supports the hypothesis that FinTech companies have an effect on the financial stability of banks. The findings are consistent with a wide variety of model specifications, indices of financial stability, and applications of FinTech. This study is unique and contributes to the extant literature by offering new evidence on the effect of FinTech on the sustainability of banks in GCC. Other Information Published in: Corporate Governance and Organizational Behavior Review License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.22495/cgobrv6i4sip16 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.